Providers' and Survivors' Perspectives on Affordability Challenges for Gastrointestinal Cancer Treatment in Two Low Socioeconomic Status States of the Southern United States - Maria Pisu; Nataliya V. Ivankova; Jessica Morgan; Courtney P. Williams; Nathan C. English; Burkely P. Smith; Bayley A. Jones; Wendelyn M. Oslock; Yu‐Mei Schoenberger; Ivan I. Herbey; Daniel I. Chu (Cancer Medicine)
ABSTRACT Introduction Affordability is an access to care domain contributing to disparities in gastrointestinal (GI) cancer outcomes and care, including surgical care. Affordability challenges for GI cancer care in socioeconomically disadvantaged and diverse states of the southern United States are unknown: this paper addresses this knowledge gap. Methods We conducted semi‐structured interviews with 32 providers (13 surgeons and 19 other) and 36 survivors (53% colorectal, 19% pancreatic, and 28% esophageal cancer) in Alabama and Mississippi. Questions were about barriers and facilitators to surgical care along five domains, including affordability, that is, the relationship between health care costs, patients' income, health insurance coverage, and the resulting ability to afford care. Verbatim transcripts were analyzed using thematic and content analysis. Results Themes were about: (1) affordability‐related underlying context, that is, (i) patients' limited means and competing basic needs priorities, (ii) scarcity of quality medical services, and (iii) rural hospitals' limited means; (2) barriers to medical decision‐making, that is, (i) guideline‐concordant care unfeasible due to poverty and (ii) insurance authorizations and coverage delaying and making care costlier; (3) economic burdens from (i) many types of needed expenses and (ii) billing; and (4) strategies to improve affordability, that is, (i) care adjustments to reduce patients' costs, (ii) community organizations' support, and (iii) burdensome access to resources. Conclusions Underlying poverty, scarce quality medical services, and restrictive insurance provisions significantly impact medical decision‐making, access to quality and prompt care, and economic and administrative burdens. Future research should quantify the extent of these challenges and identify programs and policies to address them.